Georeferencing Strategies in Very Shallow Waters: A Novel GCPs Survey Approach for UCH Photogrammetric Documentation - Alessio Calantropio; Filiberto Chiabrando (Remote Sensing, 2024)
The growing interest of the scientific community in surveying and monitoring submerged assets is motivated by the increasing demand for high-resolution products with certified accuracies. While many instrumental and methodological solutions for documenting, monitoring, and studying archaeological and cultural heritage through geomatics techniques are already available for the terrestrial environment, the challenge remains open to the underwater context. High-resolution capability and accurate positioning are still difficult to achieve in these environments. This paper discusses the limitations of positioning and georeferencing techniques in the underwater environment. It explores how existing methods and new instruments can be used to perform accurate topographic surveys of ground control points (GCPs) in very shallow waters (within 5 m depths), which can support the photogrammetric reconstruction of underwater assets. This research presents two innovative prototypes: a self-built plastic marker for topographic use in the underwater environment and a self-built aluminum pole for topographic use in the marine environment. The prototypes are tested and validated with a tilt-compensating smart antenna to reduce planar and altimetric errors when the pole is not perfectly level and to work independently of the shore proximity required when using a total station to perform said measurements.